A within-subject comparison of the conventional clasp-retained with attachment-retained removable partial dentures. Issue 4 (August 2020) - Alqutaibi, Ahmed Y.
الملخص: أهداف البحث: تقييم رضا المرضى عن أطقم الأسنان الجزئية بالمشابك التقليدية مقابل تلك التي تعتمد على الثبات عن طريق الملحقات الدقيقة عند إعادة تأهيل الفك العلوي. طرق البحث: تتضمن هذه الدراسة ١٠ مرضى يعانون من فقدان جزئي للأسنان العلوية تم تعويضها بتركيبات جزئية متحركة بمشابك تقليدية، وتم متابعتها على مدى ثلاثة أشهر من ثم تم استبدالها بتركيبات أخرى تعتمد على الملحقات الدقيقة، وتم متابعتها لثلاثة أشهر أخرى من دون عمل فترة راحة بين التركيبتين. خلال هذه الفترة طلب من المرضي تعبئة استبانة عن رضائهم عن التركيبات، وتشمل الاستبانة أسئلة تشمل سهولة التنظيف، والمقدرة على الكلام، والراحة، والجمالية، والثبات، والمقدرة على المضغ، وكفاءة المضغ، والرضا العام. النتائج: أظهرت النتائج رضا أكثر للمرضى بالتركيبات المتحركة بالملحقات الدقيقة مقارنة بتلك المعتمدة على المشابك التقليدية، بسبب سهولة التنظيف، والمقدرة على الكلام، والراحة، والجمالية، والثبات، والمقدرة على المضغ، وكفاءة المضغ. الاستنتاجات: تمثل التركيبات المتحركة المعتمده على الملحقات الدقيقة بديل جيد عن تلك التي تعتمد على المشابك التقليدية خاصة عندما يتم تعويض الأسنان في الفك العلوي. Abstract: Objective: This study conducted to satisfaction with conventional clasp-retained and attachment-retained removable partial dentures (RPDs) among patients with partially edentulous maxilla. Methods: The crossover trial recruited 10 patients with bilateral free-end partially edentulous maxilla who received a conventional RPD for 3 months, followed by an attachment-retained removable partial denture (ARRPD) for another 3 months. There was no washout period between the two interventions. During follow-up, patients were requested to complete a patient satisfaction questionnaire. This 9-item validated questionnaire measured patient satisfaction with the ease of cleaning, ability to speak, comfort, aesthetics, stability, ability to masticate different types of food, masticatory efficiency, oral condition, and general satisfaction. Results: The comparison of the two treatment modalities showed significantly higher satisfaction with the ARRPD than with the conventional RPD. The ARRPD was preferred due to the ease to clean, speech, comfort, aesthetics, stability, masticatory ability, and masticatory efficiency ( p  < .05). Conclusion: The study showed higher short-term satisfaction rates in patients with ARRPDs than with the conventional clasp-retained RPDs. The superior aesthetics of ARRPDs are recognized in conjunction with the restoration of the partially edentulous maxilla.